Friendship Work on Facebook: Young Adults' Understandings and Practices of Friendship. (29th May 2014) - Niland, Patricia; Lyons, Antonia C.; Goodwin, Ian; Hutton, Fiona
Abstract: Young adults use social networking sites (SNSs) such as Facebook to engage as friends, yet there has been little systematic research that has investigated their sense‐making of friendship in relation to their uses of Facebook, as well as how Facebook as a socio‐technical system interacts with their friendship practices. Twelve friendship discussion groups were conducted in urban and non‐urban New Zealand, with 26 women and 25 men aged 18–25 years, in same and mixed‐gender groups. Our social constructionist thematic analysis showed the young adults made sense of friendship through themes of 'fun times together', an 'investment', 'protection' and 'self‐authenticity', and these meanings were enacted in particular ways within Facebook. This SNS was used primarily for enjoying friendship and 'investing in' friendships, and friendship protection was required to maintain friends' online privacy. Facebook provided a way to demonstrate self‐authenticity within friendship relationships through censored 'show off' self‐displays and favoured friendship activities. Facebook supported, disrupted and modified these particular friendship understandings by broadening the audience for friendship actions and intensifying friends' responses through 24/7 accessibility and instantaneous activity notifications. These interactions between friendship understandings and Facebook as a socio‐technical system demonstrate how friendship was reinforced, negotiated and re‐worked through this online context. Copyright © 2014 John Wiley & Sons, Ltd.